A novel branched polysaccharide from Rhodomyrtus tomentosa: structural elucidation, physicochemical properties and antioxidant activity - Li, Dingjin; Duan, Qiuxia; Wan Ibadullah, Wan Zunairah; Shukri, Radhiah; Gu, Yipeng; Nie, Hui; Liu, Yan; Mustapha, Nor Afizah (John Wiley and Sons, 2025)
BACKGROUND: Polysaccharides from medicinal and edible plants have attracted increasing attention as a result of their structural diversity and potential bioactivities. In this study, a novel heteropolysaccharide (RTP) was isolated and purified from Rhodomyrtus tomentosa fruits. The physicochemical properties, structural characteristics and antioxidant activities of RTP were investigated. RESULTS: The results demonstrated that the RTP was mainly formed by →6)-α-d-Glcp-(1→, →4)-α-d-Glcp-(1→, →4,6)-α-d-Glcp-(1→ and →3,6)-β-d-Galp-(1 → interconnected with each other to form a backbone. Branched chains were mainly formed by α-l-Araf-(1 → attached to the O-6 position of the glycosyl residue →3,6)-β-d-Galp-(1→ and α-d-Glcp-(1 → attached to the O-6 position of the glycosyl residue →4,6)-α-d-Glcp-(1→. RTP exhibited excellent thermal stability. The maximum scavenging rates of 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (i.e. ABTS) and hydroxyl radicals by RTP were 97.78 ± 1.08% and 98.17 ± 0.57%, respectively. CONCLUSION: Polysaccharide from R. tomentosa may serve as a promising natural antioxidant for developing functional foods and therapeutic agents. © 2025 Society of Chemical Industry.